Positive electrode material for sodium ion battery, preparation method of positive electrode material, positive electrode composition, sodium ion secondary battery and application
By adopting a combined structure of layered oxide core and cladding in the positive electrode material of sodium ion battery, the problems of nickel oxide heterophase and residual alkali heterophase under high nickel content are solved, and the electrochemical performance of the material is significantly improved, especially the cyclic performance under high temperature and high magnification conditions.
Patent Information
- Application Number
- CN202411776550.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing sodium ion layered oxide positive electrode materials are prone to form nickel oxide heterophase and residual alkali heterophase when they are high nickel content, resulting in a decrease in electrochemical performance, especially the significant deterioration of the circulation performance.
A positive electrode material for sodium ion batteries is used, which includes a layered oxide core and a cladding layer, and the overall composition is Na1+2xNiu+x(1+y)Cox(1-y)M1-uO2+δ. The cladding layer is represented by Na2Ni1+yCo1-yAαO4+β. By controlling the composition of the core and cladding layer, the nickel oxide heterophase is eliminated and the residual alkali content is reduced, and the conductivity and cycling performance are improved.
Through this technical method, the nickel oxide heterophase is eliminated and the residual alkali content is reduced, the initial discharge capacity and cycling performance of the positive electrode material are improved, and the performance is better in high temperature and high magnification conditions.
Smart Images

Figure CN119581530A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of energy storage technology, in particular to the field of sodium ion secondary batteries. Specifically, the present invention relates to a positive electrode material for a sodium ion battery, a preparation method thereof, a positive electrode composition comprising the positive electrode material, a sodium ion secondary battery comprising the positive electrode composition, and uses of the sodium ion secondary battery. Background Art
[0002] Since sodium ions have the advantages of abundant resources and cheap raw materials, sodium ion secondary batteries are considered to be very likely to replace lithium ion secondary batteries to solve the problem of lithium resource shortage, thereby achieving cheap large-scale energy storage and large-scale commercial applications.
[0003] However, the atomic mass of sodium ions is relatively large, which results in a lower theoretical capacity of sodium ion layered oxide cathode materials than that of lithium ion layered oxide cathode materials, which further results in a lower actual energy density. The energy density of sodium ion layered oxide cathode materials can be improved by adjusting the material system and the combination of various elements. The main ideas are: (1) increasing the specific capacity of active materials, and (2) increasing the upper limit of discharge voltage to exert more reversible specific capacity and increase the battery operating voltage.
[0004] One of the current technical routes for high-capacity O3-phase sodium-ion layered oxide positive electrode materials is to increase the proportion of nickel in the material. Nickel has high electrochemical activity, and a single nickel atom can switch between Ni2+ / Ni3+ / Ni4+ valence states, providing a theoretical basis for high-capacity positive electrode materials. However, with the increase of Ni content, sodium-ion layered oxide positive electrode materials tend to generate a more obvious nickel oxide impurity phase, or a residual alkali impurity phase, which is not conducive to the electrochemical performance, especially causing a significant deterioration in the cycle performance.
[0005] Therefore, for layered oxide cathode materials with high nickel content in the O3 phase, there is still a need to improve their electrochemical performance. Summary of the invention
[0006] The present invention is made in view of the above problems existing in the prior art.
[0007] In a first aspect, the present invention relates to a positive electrode material for a sodium ion battery, comprising:
[0008] a layered oxide core and a layered oxide coating formed on the core,
[0009] The positive electrode material has the following composition as a whole:
[0010] Na 1+2x Ni u+x(1+y) Co x(1-y) M 1-u O2+δ
[0011] The coating layer is represented by the following formula:
[0012] Na2Ni 1+y Co 1-y A α O 4+β
[0013] And the molar ratio of the coating layer to the core is x,
[0014] in
[0015] x = 0.01-0.03,
[0016] u=0.40-0.49,
[0017] y = -0.10 to 0.10,
[0018] M is at least two elements selected from the group consisting of metal elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, including Cu and Mn,
[0019] δ = -0.40 to 0.40,
[0020] A is a part or all of the elements selected from the M elements,
[0021] 0<α<1,
[0022] 0<β<2.
[0023] In a second aspect, the present invention relates to a method for preparing the positive electrode material of the first aspect, comprising the following steps:
[0024] Preparation of the inner core: Na source, Ni source and M source are uniformly mixed in a molar ratio of Na, Ni and M elements of (1+2x):(u+x(1+y)):(1-u), and first sintered at a first temperature of 850-1000° C. in an oxygen-containing atmosphere, followed by cooling, and optionally pulverizing and screening to obtain an inner core substrate, wherein the Na source (Na element) and the Ni source (Ni element) are in molar excess of 2x and x(1+y), respectively, relative to the composition stoichiometry of the inner core; and
[0025] Preparation of the coating layer: The prepared core substrate and the Co source are uniformly mixed according to the molar ratio of the excess Ni element amount and the Co element amount in the preparation of the core (1+y) / (1-y), and then a second sintering is carried out in an oxygen-containing atmosphere at a second temperature of 800-980°C lower than the first temperature, followed by cooling and optionally crushing and screening to obtain the positive electrode material.
[0026] In a third aspect, the present invention relates to a positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the positive electrode material for a sodium ion battery according to the first aspect of the present invention.
[0027] In a fourth aspect, the present invention relates to a sodium ion secondary battery comprising the positive electrode composition of the third aspect of the present invention.
[0028] In a fifth aspect, the present invention relates to the use of the sodium ion secondary battery of the fourth aspect of the present invention in an energy storage device, especially an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0029] The applicant has found that by controlling the overall composition of the positive electrode material and the composition of the coating layer (and therefore the composition of the core, in other words, controlling the composition of the core and the coating layer and therefore the overall composition of the positive electrode material), in particular, by using the Ni source and the Na source in excess in a specific amount when preparing the core, and then controlling the ratio between the Co source used in the coating layer and the excess Ni source when preparing the core when forming the coating layer, so that the excess Ni source and Na source when preparing the core are consumed for the coating layer, the prepared positive electrode material and the coating layer (and therefore the core) have a defined composition, thereby eliminating the nickel oxide impurity phase that is easily present under conventional sintering conditions, reducing the residual alkali content, and / or improving the powder (electronic) conductivity; relative to the positive electrode material having a composition outside the defined range, the resulting positive electrode material can improve the initial discharge capacity and cycle performance (especially high temperature cycle performance at high rates (e.g., 1C)). BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solution of the present invention, the following is a brief description of the drawings required for describing the embodiments. It should be understood that these drawings are only for the purpose of facilitating technicians to more easily understand the present invention, and are not intended to limit the scope of the present invention, among which:
[0031] Figure 1-3 Scanning electron microscope (SEM) images of the positive electrode materials prepared in Examples 1-3 at a magnification of 10,000 times are shown respectively.
[0032] Figure 4 The XRD spectra of the core substrate prepared in Example 4 and the final positive electrode material after coating are shown.
[0033] Figure 5 The first charge and discharge curve of the positive electrode material prepared in Example 5 is shown. DETAILED DESCRIPTION
[0034] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.
[0035] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.
[0036] In the present application, unless otherwise specified, the temperature is room temperature (25° C.), the atmosphere is air, and the pressure is atmospheric pressure.
[0037] Those skilled in the art will understand that in the present application, unless otherwise specified, a number containing n significant digits after the decimal point actually also covers the result of rounding a number containing more significant digits after the decimal point to n significant digits after the decimal point. For example, 1.0 actually covers all numbers in the range from greater than or equal to 0.95 to less than 1.05; 0.16 actually covers all numbers in the range from greater than or equal to 0.155 to less than 0.165; 0.166 actually covers all numbers in the range from greater than or equal to 0.1655 to less than 0.1665, and so on.
[0038] The present invention relates to a positive electrode material for a sodium ion battery, a preparation method thereof, a positive electrode composition comprising the positive electrode material, a sodium ion secondary battery comprising the positive electrode composition, and uses of the sodium ion secondary battery.
[0039] The present invention will be described in detail below.
[0040] Cathode Materials
[0041] In a first aspect, the present invention relates to a positive electrode material for a sodium ion battery, comprising:
[0042] a layered oxide core and a layered oxide coating formed on the core,
[0043] The positive electrode material has the following composition as a whole:
[0044] Na 1+2x Ni u+x(1+y) Co x(1-y) M 1-u O 2+δ
[0045] The coating layer is represented by the following formula:
[0046] Na2Ni 1+y Co 1-y A α O 4+β
[0047] And the molar ratio of the coating layer to the core is x,
[0048] in
[0049] x = 0.01-0.03,
[0050] u=0.40-0.49,
[0051] y = -0.10 to 0.10,
[0052] M is at least two elements selected from the group consisting of metal elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, including Cu and Mn,
[0053] δ = -0.40 to 0.40,
[0054] A is a part or all of the elements selected from the M elements,
[0055] 0<α<1,
[0056] 0<β<2.
[0057] The applicant has found that when the positive electrode material has a defined overall composition and coating layer composition (and therefore has a specific core composition), it is possible to eliminate the nickel oxide impurity phase that is easily present under conventional sintering conditions, reduce the residual alkali content, and / or improve the powder (electronic) conductivity. Relative to the positive electrode material having a composition outside the defined range, the resulting positive electrode material is able to improve the initial discharge capacity and cycle performance (especially high temperature cycle performance at high rates (e.g., 1C)).
[0058] In an embodiment, the molar ratio of the coating layer to the core (i.e., the molar ratio of the coating layer according to its composition formula and the core according to the molar ratio of the composition formula obtained by deducting the composition of the coating layer from the overall composition formula of the positive electrode material) x = 0.01-0.03, such as 0.01, 0.02, 0.03, or a range defined by any two thereof. Within the defined range, relative to other ranges (such as lower x (including the case of containing less coating layer and no coating layer) or higher x), the initial discharge capacity and cycle performance (such as high-temperature cycle retention rate at high rate (such as 1C)) of the obtained positive electrode material can be improved.
[0059] In an embodiment, u=0.40-0.49; for example, u may be 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, or a range defined by any two of them. Within the defined range, the obtained positive electrode material can achieve improved initial discharge capacity and cycle performance (e.g., high temperature cycle retention rate at high rate (e.g., 1C)).
[0060] In an embodiment, y=-0.10 to 0.10, for example, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two of them; preferably, y=-0.05 to 0.05, for example, y=-0.02 to 0.02, for example, 0. Within the defined range (for example, relative to the case where the coating layer does not contain Na and / or Ni and / or the Ni / Co ratio is outside the range, for example, the coating layer contains a lower ratio of Ni, or even contains no Ni, or contains a higher ratio of Ni), the initial discharge capacity and cycle performance (for example, high temperature cycle retention rate at high rate (for example, 1C)) of the resulting positive electrode material can be improved.
[0061] In an embodiment, the M element is at least two elements selected from the group consisting of metal elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y and includes Cu and Mn; preferably, M may be at least two elements selected from the group consisting of metal elements Cu, Fe, Mn, Ti, Mg, Zn, Al, Zr, Sn, and Y and includes Cu and Mn.
[0062] In a preferred embodiment, M includes or is Cu and Mn.
[0063] In a preferred embodiment, M includes or is Cu, Mn and Ti.
[0064] In a preferred embodiment, M comprises Cu, Mn and Ti, and optionally further comprises one or more elements selected from Fe, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, Y, preferably, one or more elements selected from Fe, Mg, Zn, Al, Zr, Sn, Y.
[0065] In an embodiment, the subscript of the M element in the positive electrode material is 1-u, that is, 0.51-0.60, for example, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, or a range limited by any two thereof.
[0066] In an embodiment, δ = -0.40 to 0.40, for example, -0.40, -0.39, -0.38, -0.37, -0.36, -0.35, -0.34, -0.33, -0.32, -0.31, -0.30, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.06 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, or a range defined by any two of them.
[0067] In an embodiment, the coating layer includes Na, Ni and Co elements and further includes an A element. The A element is a part or all of the elements selected from the M element (in terms of element type); preferably, the A element is the same as the M element (in terms of element type). Preferably, the A element comes from the M element used in the preparation process of the core; that is, the A element is not added during the coating process.
[0068] In an embodiment, the subscript α of the A element in the coating layer satisfies 0<α<1, for example, α can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.2 1. 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48 , 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75 , 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range limited by any two of them.
[0069] In an embodiment, the subscript β of the O element in the coating layer satisfies the chemical formula balance, and 0<β<2, β may vary according to the valence and content of the A element in the coating layer, for example, β may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 8, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.6 3. 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.8 8, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1. 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.30, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1. 38, 1.39, 1.40, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.50, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1.60, 1.61, 1.62, 1. 63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69, 1.70, 1.71, 1.72, 1.73, 1.74, 1.75, 1.76, 1.77, 1.78, 1.79, 1.80, 1.81, 1.82, 1.83, 1.84, 1.85, 1.86, 1.87, 1.88, 1.89, 1.90, 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97, 1.98, 1.99, or a range defined by any two of them. .
[0070] In an embodiment, the sum of the subscripts of Co and Ni in the coating layer is 2, and thus the ratio relative to the subscript of the Na element in the coating layer is 1:1.
[0071] The positive electrode material of the present invention does not show a nickel oxide impurity peak in X-ray diffraction spectrum (XRD) analysis. In the present application, the expression "no nickel oxide impurity peak" or "no nickel oxide peak" means that the diffraction intensity of the nickel oxide peak in XRD is lower than the background noise intensity.
[0072] In an embodiment, the core may have the following composition:
[0073] NeNi u M 1-u-αx O 2+γ
[0074] Where: u, α and x are as defined above;
[0075] γ = -0.40 to 0.40, for example -0.40, -0.39, -0.38, -0.37, -0.36, -0.35, -0.34, -0.33, -0.32, -0.31, -0.30, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.0 4. -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, or a range defined by any two of them.
[0076] Those skilled in the art will understand that the subscripts of the elements in the positive electrode material (i.e., x, u, y, δ, α, β, and γ) will satisfy the valence balance, that is, the positive electrode material, its core and coating are each electrically neutral as a whole. In the present application, including in the embodiments, for the subscripts of the oxygen element in the positive electrode material and its core (e.g., δ, and γ), even if they are not equal to 2, sometimes for the sake of convenience, they are directly recorded as "2", "2.0" or "2.00", which is also a common representation of the subscript O in the art. However, those skilled in the art will understand that for the case where the subscript of the oxygen element is not equal to 2, even if it is recorded as "2", it actually represents a meaning similar to "2+δ" (e.g., δ=-0.40 to 0.40), and according to the ratio of the raw materials used and the valence of the relevant elements in the raw materials, those skilled in the art will understand and can easily calculate that the value actually represented by the subscript 2 of the oxygen element in this case is completely within the capabilities of those skilled in the art.
[0077] Those skilled in the art will appreciate that the positive electrode material, the core and the coating may also contain other elements at impurity levels. For example, the core may contain cobalt elements that diffuse from the coating layer into the core during the formation of the coating layer. However, since the molar ratio of the coating layer to the core is relatively low and the diffused cobalt element accounts for only a very small portion of the cobalt element used in preparing the coating layer, very little cobalt element enters the core, so that the change in the content of cobalt element in the coating layer and the content of cobalt element in the core can be ignored.
[0078] A portion of the M element contained in the core may diffuse into the coating layer when the core is subsequently coated, which is understandable to those skilled in the art. In the present application, sometimes for convenience (for example, in the embodiments), the above composition formula of the core is also (according to the composition of the raw materials used when the core is initially prepared) NaNi u M 1-u-αx O 2+γ Abbreviated as NaNi u M 1- u O2, which does not deviate from the scope of the present invention; those skilled in the art will understand that the core composition of this notation should actually be deducted from the part of the M element diffused into the coating layer, that is, it still represents the above-mentioned NaNi u M 1-u-αx O 2+γ ; and based on the given overall composition of the positive electrode material and the composition of the coating layer, the actual composition of the core can be easily determined.
[0079] In an embodiment, the core and the coating layer of the positive electrode material may both belong to the R-3m space group and have an O3 phase crystal structure.
[0080] In an embodiment, the subscript of the M element in the overall composition of the positive electrode material satisfies 1-u, that is, 0.51-0.60 and / or the subscript of the M element in the composition of the core may satisfy 1-u-αx; under this premise, the positive electrode material may further satisfy one or more of the following conditions:
[0081] When M includes Mn, the subscript of Mn in the overall composition of the positive electrode material and / or the composition of the core can be independently, for example, 0.30-0.59, for example, 0.40-0.51, for example, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, or a range defined by any two of them; and / or
[0082] When M includes Cu, the subscript of Cu in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.20, such as 0.01-0.10, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or a range defined by any two thereof; and / or
[0083] When M includes Ti, the subscript of Ti in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.20, such as 0.01-0.10, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or a range defined by any two thereof; and / or
[0084] When M includes Fe, the subscript of Fe in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0085] When M includes Al, the subscript of Al in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0086] When M includes Y, the subscript of Y in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0087] When M includes Mg, the subscript of Mg in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0088] When M includes Zn, the subscript of Zn in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0089] When M includes Zr, the subscript of Zr in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0090] When M includes Sn, the subscript of Sn in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0091] When M includes Li, the subscript of Li in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0092] When M includes Ca, the subscript of Ca in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0093] When M includes Ta, the subscript of Ta in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0094] When M includes Mo, the subscript of Mo in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0095] When M includes W, the subscript of W in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0096] When M includes La, the subscript of La in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0097] When M includes Sr, the subscript of Sr in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0098] When M includes Sb, the subscript of Sb in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0099] When M includes Ce, the subscript of Ce in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, such as 0.01-0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0100] When M includes Nb, the subscript of Nb in the overall composition of the positive electrode material and / or the composition of the core can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range limited by any two of them.
[0101] The positive electrode material may have, for example, a Dv50 particle size as follows: 1-100 μm, for example 5-20 μm, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 μm, or a range defined by any two thereof. In the present application, unless otherwise specified, particle size D50 refers to a particle size of 50% of the volume of particles in a volume cumulative distribution curve that is lower than the particle size value. Particle size can be measured, for example, by a laser scattering method commonly used in the art. For example, it can be measured using a Malvern particle size analyzer commonly used in the art, such as a MASTERSIZER-3000 or other instrument.
[0102] The positive electrode material may have a residual alkali content of less than 0.5%, such as 0.1-0.5%, such as 0.1-0.4%, such as 0.1, 0.2, 0.3, 0.4, 0.5%, or a range limited by any two thereof.
[0103] By controlling the overall composition of the positive electrode material and the composition of the coating layer (and therefore the composition of the core, in other words, controlling the composition of the core and the coating layer and therefore the overall composition of the positive electrode material), the resulting positive electrode material has excellent electrochemical properties, such as improved initial discharge capacity and improved cycle performance (such as high rate (e.g. 1C) high temperature (e.g. 45°C) cycle characteristics) relative to positive electrode materials having a composition outside the specified range.
[0104] Preparation method of positive electrode material
[0105] In a second aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery according to the first aspect of the present invention, comprising the following steps:
[0106] Preparation of the inner core: mixing a Na source, a Ni source and an M source uniformly according to a molar ratio of Na, Ni and M elements of (1+2x):(u+x(1+y)):(1-u), and performing a first sintering at a first temperature of 850-1000° C. in an oxygen-containing atmosphere, followed by cooling, and optionally pulverizing and screening to obtain an inner core substrate, wherein the Na source and the Ni source are in molar excess of 2x and x(1+y) respectively relative to the composition stoichiometry of the inner core; and
[0107] Preparation of the coating layer: The prepared core substrate and the Co source are uniformly mixed according to the molar ratio of the excess Ni element amount and the Co element amount in the preparation of the core (1+y) / (1-y), and then a second sintering is carried out in an oxygen-containing atmosphere at a second temperature of 800-980°C lower than the first temperature, followed by cooling and optionally crushing and screening to obtain the positive electrode material.
[0108] Each step will be described in detail below.
[0109] Preparation of the kernel
[0110] The preparation steps of the inner core can be carried out as follows: Na source, Ni source and M source are uniformly mixed according to the molar ratio of Na, Ni and M elements being (1+2x):(u+x(1+y)):(1-u), and a first sintering is carried out at a first temperature of 850-1000°C in an oxygen-containing atmosphere, followed by cooling, and optionally crushing and screening to obtain an inner core substrate, wherein relative to the compositional stoichiometry of the inner core (relative to the amount of Na in the inner core (Na subscript is calculated as 1), the same below), the Na source and the Ni source are in molar excess of 2x and x(1+y), respectively.
[0111] During mixing, the Na source and the Ni source are used in excess relative to the stoichiometric composition of the core, and the excess amounts correspond to the Na and Ni elemental compositions in the coating layer, i.e., the Na and Ni elements in the coating layer originate from the excess Na source and Ni source here.
[0112] The meanings of x, u, and y are the same as those described above and will not be repeated here.
[0113] The sodium source used is not particularly limited, and may be any sodium-containing compound known to those skilled in the art for preparing a positive electrode material for a sodium ion secondary battery. Preferably, the sodium source ultimately does not introduce other elements other than the elements constituting the layered oxide positive electrode material. The sodium source may be one or more in the form of an oxide, hydroxide, salt, etc. containing sodium. In one embodiment, the Na source may be one or more selected from the following compounds: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, sodium chloride, sodium sulfate, and sodium oxide.
[0114] The Ni source used is not particularly limited, and may be any nickel-containing compound known to those skilled in the art for preparing a positive electrode material for a sodium ion secondary battery. Preferably, the nickel source ultimately does not introduce other elements other than the elements constituting the layered oxide positive electrode material. The metal in the Ni source may contain only metallic Ni, or may contain other metals contained in the core of the positive electrode material in addition to Ni, in which case the Ni source may be a composite metal compound. In one embodiment, the Ni source may be one or more selected from the following compounds: nickel carbonate, nickel nitrate, nickel acetate, nickel oxalate, nickel hydroxide, nickel sulfate, nickel chloride, nickel oxide, nickel manganese hydroxide, copper nickel manganese titanium carbonate.
[0115] Those skilled in the art will appreciate that, in the present application, “no other elements other than the elements constituting the layered oxide positive electrode material are introduced” means that the other elements are not intentionally introduced, which means that the other elements may be introduced into the positive electrode material at impurity levels.
[0116] The M source is not particularly limited and can be appropriately selected from any M-containing compound known to those skilled in the art for preparing a positive electrode material for a sodium ion secondary battery according to the overall composition of the positive electrode material and the composition of the inner core. The M source can be provided in the following forms: (1) provided in the form of a compound containing only one of the metals contained in the inner core of the positive electrode material other than sodium (for example, only containing metal Cu, Mn, or Fe), or (2) provided in the form of a compound containing two or more of the metals contained in the inner core of the positive electrode material other than sodium (i.e., a composite metal compound containing multiple metals); or (3) any combination thereof. Preferably, the M source ultimately does not introduce other elements other than the elements constituting the layered oxide positive electrode material. The metals contained in the M element can each be provided in the form of, for example, carbonates, nitrates, sulfates, oxalates, acetates, chlorides, hydroxides, oxides; alternatively or additionally, a part or all of them can also be provided in the form of a composite metal compound such as an oxide, hydroxide and / or carbonate.
[0117] For example, the Cu source may be one or more selected from the following compounds: copper carbonate, copper nitrate, copper acetate, copper oxalate, copper hydroxide, copper sulfate, copper chloride, copper oxide, copper nickel manganese titanium carbonate; when used, the Fe source may be one or more selected from the following compounds: iron carbonate, iron nitrate, iron acetate, iron oxalate, iron hydroxide and iron oxide; the Mn source may be one or more selected from the following compounds: manganese carbonate, manganese nitrate, manganese acetate, manganese oxalate, manganese hydroxide, manganese sulfate, manganese chloride and manganese oxide (such as manganese dioxide), manganese hydroxide nickel, copper nickel manganese titanium carbonate; when used, the Ti source may be one or more selected from the following compounds: titanium nitrate, titanium oxalate, titanium hydroxide, titanium sulfate, titanium oxysulfate, titanium chloride and titanium oxide; when used, the Mg source may be one or more selected from the following compounds: magnesium nitrate, magnesium acetate, magnesium oxalate, magnesium hydroxide, magnesium sulfate, magnesium chloride, magnesium carbonate and magnesium oxide; when used, the Zn source may be one or more selected from the following compounds: zinc nitrate, zinc acetate, oxalate, When used, the Li source may be one or more selected from the following compounds: lithium nitrate, lithium oxalate, lithium acetate, lithium hydroxide, lithium sulfate, lithium chloride, lithium carbonate and lithium oxide; when used, the Al source may be one or more selected from the following compounds: aluminum carbonate, aluminum nitrate, aluminum acetate, aluminum oxalate, aluminum hydroxide and aluminum oxide; when used, the Ca source may be one or more selected from the following compounds: calcium carbonate, calcium nitrate, calcium acetate, calcium oxalate, calcium hydroxide and calcium oxide; when used, the Zr source may be one or more selected from the following compounds: zirconium carbonate, zirconium nitrate, zirconium acetate, zirconium oxalate, zirconium hydroxide and zirconium oxide; when used, the Y source may be one or more selected from the following compounds: yttrium carbonate, yttrium nitrate, yttrium acetate, yttrium oxalate, yttrium hydroxide and yttrium oxide; when used, the La source may be one or more selected from the following compounds: lanthanum carbonate, lanthanum bicarbonate, lanthanum nitrate, lanthanum acetate, lanthanum oxalate, lanthanum hydroxide and lanthanum oxide
[0118] The mixing can be carried out in any suitable mixing manner known to those skilled in the art, for example, by dry mixing or wet mixing. The wet mixing can be carried out in the presence of any suitable solvent, such as water or ethanol.
[0119] The oxygen-containing atmosphere is not particularly limited and may be, for example, air, oxygen or compressed air. The pressure of the oxygen-containing atmosphere is not particularly limited and may be any commonly used pressure, for example, 0.1 MPa or more, for example, 0.1-1.0 MPa, for example, 0.3-0.7 MPa. The flow rate of the oxygen-containing atmosphere is not particularly limited and may be, for example, 5-20 L / (min·kg), where kg refers to the mass of the sintered mixture on a dry weight basis.
[0120] The first sintering temperature is 850-1000° C., for example, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000° C., or within the range defined by any two of them.
[0121] The time for the first sintering is not particularly limited, and may be, for example, 10-48 hours, for example 10-30 hours, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48 hours, or a range limited by any two thereof.
[0122] The heating rate during the first sintering is not particularly limited, and may be, for example, 1-10°C / min, such as 2-5°C / min, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10°C / min, or within the range defined by any two of them.
[0123] After the first sintering, cooling is performed, and optionally crushing and screening is performed to obtain the core substrate. The cooling, crushing and screening can be performed by any suitable means known to those skilled in the art. For example, the cooling can be natural cooling, air cooling or water cooling. For example, the crushing can be air flow crushing or mechanical crushing.
[0124] The core substrate may be crushed to a Dv50 particle size of, for example, 1-100 μm, such as 5-20 μm. For example, the D50 particle size of the particles may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 μm, or a range defined by any two thereof.
[0125] Preparation of coating layer
[0126] In the step of preparing the coating layer, the prepared core substrate is coated, wherein the core substrate prepared as above is uniformly mixed with a Co source according to a molar ratio of (1+y) / (1-y) between the excess Ni element amount and the Co element amount in the preparation of the core, and then a second sintering is carried out in an oxygen-containing atmosphere at a second temperature of 800-980°C lower than the first temperature, followed by cooling and optionally crushing and screening to obtain the positive electrode material.
[0127] In an embodiment, the core substrate prepared as above is uniformly mixed with the Co source according to the molar ratio of the excess Ni element amount and the Co element amount in the preparation of the core (1+y) / (1-y). In the preparation of the core, the Ni source (Ni element) has a molar excess of x(1+y) relative to the composition stoichiometry of the core, so in this step, the addition amount of the Co element is x(1-y).
[0128] The meanings of x and y are the same as those described above and will not be repeated here.
[0129] The Co source is not particularly limited and can be any cobalt-containing compound known to those skilled in the art for preparing a positive electrode material for a sodium ion secondary battery. In one embodiment, the cobalt source can be one or more selected from the following compounds: cobalt carbonate, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt hydroxide, cobalt sulfate, cobalt chloride, cobalt oxide.
[0130] The oxygen-containing atmosphere is not particularly limited and may be, for example, air, oxygen or compressed air. The pressure of the oxygen-containing atmosphere is not particularly limited and may be any commonly used pressure, for example, 0.1 MPa or more, for example, 0.1-1.0 MPa, for example, 0.15-0.5 MPa. The flow rate of the oxygen-containing atmosphere is not particularly limited and may be, for example, 5-20 L / (min·kg), where kg refers to the mass of the sintered mixture on a dry weight basis.
[0131] The second temperature is lower than the first temperature. For example, the second temperature may be 10-200°C, such as 10-150°C, such as 20-100°C, such as 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200°C, or a range defined by any two of them, lower than the first temperature.
[0132] The second temperature may be 800-980°C, for example, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980°C, or a range defined by any two thereof.
[0133] The time for the second sintering is not particularly limited, and may be 10-48 hours, for example 10-30 hours, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48 hours, or a range limited by any two of them.
[0134] The heating rate during the second sintering is not particularly limited, and may be, for example, 1-10°C / min, such as 2-5°C / min, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10°C / min, or within the range defined by any two of them.
[0135] After the second sintering, cooling is performed, and optionally pulverization and screening is performed to obtain the positive electrode material. The cooling, pulverization and screening can be performed by any suitable means known to those skilled in the art. For example, the cooling can be natural cooling, air cooling or water cooling. For example, the pulverization can be air flow pulverization or mechanical pulverization.
[0136] The positive electrode material may be crushed to a Dv50 particle size of, for example, 1-100 μm, for example, 5-20 μm. For example, the D50 particle size of the particles may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 μm, or a range defined by any two thereof.
[0137] By using Ni source and Na source in excess in a specific amount when preparing the inner core, and then controlling the ratio between the Co source used for the coating layer and the Ni source in excess when preparing the inner core when forming the coating layer, so that the excess Ni source and Na source in the preparation of the inner core are consumed for the coating layer, the inner core and the coating layer of the prepared positive electrode material have a defined composition, thereby eliminating the nickel oxide impurity phase that is easily present under conventional sintering conditions, reducing the residual alkali content, and / or improving the powder (electronic) conductivity; relative to the positive electrode material whose composition is outside the defined range, the obtained positive electrode material can improve the initial discharge capacity and cycle performance (especially the high temperature cycle performance at high rate (e.g. 1C)).
[0138] All the above descriptions about the positive electrode material of the first aspect of the present invention are applicable here.
[0139] Positive electrode composition
[0140] The third aspect of the present invention provides a positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the positive electrode material for a sodium ion battery according to the first aspect of the present invention or the positive electrode material for a sodium ion battery prepared by the method of the second aspect of the present invention.
[0141] In addition to the cathode material of the present invention, the cathode composition for a sodium ion secondary battery may further include a conductive agent, a binder, and any other substances that can be used by those skilled in the art as needed, such as a dispersant and an additive for improving stability.
[0142] In some embodiments, based on the dry weight of the positive electrode composition for a sodium ion secondary battery, the content of the positive electrode material may be a common amount in the art, for example, 70-95 wt %, for example 80-90 wt %.
[0143] The type of conductive agent is not particularly limited, as long as it has the property of enhancing the conductivity of the positive electrode and does not adversely affect the performance of the positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As an example, the conductive agent for the positive electrode composition for the sodium ion secondary battery can be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0144] In some embodiments, based on the dry weight of the positive electrode composition for a sodium ion secondary battery, the content of the conductive agent may be a common amount in the art, for example, 1-10 wt %, for example, 2-5 wt %.
[0145] The binder is not particularly limited as long as it has the properties of enhancing the adhesion between the positive electrode active material particles and the adhesion to the current collector and does not adversely affect the performance of the positive electrode material. Those skilled in the art can select according to actual needs. As an example, the binder for the positive electrode composition for the sodium ion secondary battery can be selected from polyfluoroolefin binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives and styrene-butadiene rubber, acrylic resin, carboxymethyl cellulose, polyvinyl alcohol (PVA), etc. One or more.
[0146] In some embodiments, based on the dry weight of the positive electrode composition for a sodium ion secondary battery, the content of the binder is 1-10 wt %, for example, 2-5 wt %.
[0147] The positive electrode composition may be in the form of a slurry, that is, it may further include a solvent. The positive electrode composition may also be in a dry form, that is, it does not include a solvent, for example, it may be in the form of a positive electrode active material layer disposed on a positive electrode current collector.
[0148] Sodium ion secondary battery
[0149] A fourth aspect of the present invention provides a sodium ion secondary battery. A sodium ion secondary battery generally includes a positive electrode, a negative electrode, a separator and an electrolyte.
[0150] In some embodiments, the sodium ion secondary battery may further include an outer package for encapsulating the electrode assembly and the electrolyte. For example, the outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc., or a soft package, such as a bag-type soft package, such as a soft package made of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0151] The shape of the sodium ion secondary battery is not particularly limited, and it may be cylindrical, square, or any other shape.
[0152] The sodium ion secondary battery can be prepared by a method commonly used in the art. For example, the positive electrode sheet, the negative electrode sheet and the separator can be made into a battery cell through a winding process or a lamination process, and then the electrolyte is injected.
[0153] positive electrode
[0154] The positive electrode (or positive electrode sheet) comprises a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising the positive active material composition of the third aspect of the present invention, for example in dry form. The positive electrode also forms an aspect of the present invention.
[0155] The positive electrode current collector is not particularly limited, and the positive electrode current collector commonly used by those skilled in the art may be used. As an example, the positive electrode current collector may be a metal foil such as aluminum foil, nickel foil, or a composite current collector. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), 1,3-propane sultone (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0156] The positive electrode sheet can be prepared according to the method commonly used in the art.
[0157] For example, the positive electrode can be formed by uniformly dispersing a positive electrode active material, a conductive agent, and a binder in a solvent (eg, N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; coating the slurry on a positive electrode current collector, drying, and pressing.
[0158] Alternatively, the positive electrode can also be formed by uniformly dispersing the positive electrode active material, the conductive agent, and the binder in a solvent (e.g., N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; casting the positive electrode slurry on a separate carrier, drying, separating the obtained positive electrode film from the carrier and laminating it on a positive electrode current collector.
[0159] negative electrode
[0160] The negative electrode (or negative electrode plate) can be a metal sodium plate or other commonly used negative electrodes, such as a negative electrode including a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0161] The negative electrode current collector is not particularly limited, and the negative electrode current collector commonly used by those skilled in the art can be used. As an example, the negative electrode current collector can be a metal foil such as copper foil, or a composite current collector. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0162] In some embodiments, the negative electrode active material may be an active material commonly used by those skilled in the art. For example, the negative electrode active material may be one or more of hard carbon, soft carbon, silicon-based materials, tin-based materials, sodium titanate, and metallic sodium. Among them, the silicon-based material may be one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys, and the tin-based material may be one or more of elemental tin, tin oxide compounds, and tin alloys.
[0163] In addition to the negative electrode active material, the negative electrode active material layer may further include a binder, a conductive agent and any other optional auxiliary agents such as a thickener.
[0164] There is no particular requirement for the negative electrode conductive agent. As an example, the conductive agent can be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0165] In some embodiments, the conductive agent may be present in an amount of 1 to 10 wt %, for example 2 to 5 wt %, based on the total weight (dry weight) of the negative electrode active material layer.
[0166] There is no special requirement for the negative electrode binder. As an example, the binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), styrene butadiene rubber (SBR), water-based acrylic resin and carboxymethyl cellulose (CMC).
[0167] In some embodiments, the binder may be present in an amount of 1 to 10 wt %, for example 2 to 5 wt %, based on the total weight (dry weight) of the negative electrode active material layer.
[0168] The negative electrode can be prepared according to a method commonly used in the art.
[0169] For example, the negative electrode can be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (such as N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; coating the negative electrode slurry on a negative electrode current collector, drying, and pressing.
[0170] Alternatively, the negative electrode can also be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (e.g., N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; casting the negative electrode slurry on a separate carrier, drying, separating the obtained negative electrode film from the carrier and laminating it on a negative electrode current collector.
[0171] Electrolytes
[0172] The electrolyte plays a role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte is not particularly limited and can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte, a gel electrolyte, and a liquid electrolyte (i.e., an electrolyte).
[0173] In some embodiments, the electrolyte is an electrolyte solution, which includes an organic aprotic solvent and an electrolyte sodium salt.
[0174] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0175] In some embodiments, the electrolyte sodium salt can be selected from one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroborate (NaBF6), sodium bis(trifluoromethylsulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium trifluoromethylsulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0176] In some embodiments, the concentration of sodium ions in the electrolyte may be 0.2 to 2 mol / L, for example 0.5-1.0 mol / L.
[0177] In some embodiments, the electrolyte may further include additives, for example, additives that help negative electrode film formation or positive electrode film formation, and additives that can improve battery performance, such as additives that improve high or low temperature performance of the battery.
[0178] Diaphragm
[0179] The separator is not particularly limited, and a commonly used porous structure separator with electrochemical stability and chemical stability can be used, for example, it can be a single layer or multilayer film of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. When a solid electrolyte is used, the separator can also be omitted.
[0180] use
[0181] The fifth aspect of the present invention provides the use of the sodium ion secondary battery according to the fourth aspect of the present invention in an energy storage device, especially an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0182] Those skilled in the art will appreciate that the sodium ion secondary battery of the fourth aspect of the present invention may also be used for other purposes. For example, the sodium ion secondary battery may be used as a power source or energy storage unit in a mobile device (e.g., a mobile phone, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, an electric bicycle, an electric scooter, etc.), an electric train, etc.
[0183] Example
[0184] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0185] 1. Test Method
[0186] 1. Residual alkali Na% test:
[0187] According to the mass ratio of positive electrode material: ethanol (analytical grade, density 0.789g / ml) = 1:20, take an appropriate amount of positive electrode material (mass is recorded as b) and add it to the corresponding amount of ethanol. Stir it magnetically at a speed of 600±20r / min for 30min so that ethanol can fully dissolve NaOH and Na2CO3 on the surface of the material. Then filter the mixture to obtain a filtrate. Use an atomic absorption spectrophotometer (Hitachi ZA3000) to test the Na + The residual Na content of the material is calculated according to the following formula:
[0188] Residual Na content = (a*(20*b / 0.789)) / b = a*20 / 0.789*1000 mg / kg (ie ppm).
[0189] The obtained result is converted into a percentage to obtain the residual alkali content based on the total weight of the positive electrode material.
[0190] 2. Scanning electron microscope-X-ray spectrometer (SEM-EDS)
[0191] The test was carried out using a Japanese Hitachi S-4800 scanning electron microscope-X-ray spectrometer with an acceleration voltage of 10kV, a magnification of 10k, general morphology photography, and elemental composition analysis of the material surface.
[0192] 3. XRD diffraction
[0193] The test was conducted using an X-ray diffractometer (model Bruker D8 ADVANCE) using a copper target (Cu-Kα) (accelerating voltage 40KV, current 40mA) (λ=1.54056nm), with a range of 10-80 degrees, a step length of 0.02 degrees, a time of 0.2s, and a total time of 712 seconds. The standard pdf card of nickel oxide refers to PDF#47-1049.
[0194] 4. Powder conductivity test:
[0195] A powder resistivity meter (Guangzhou Sanhao Instrument Co., Ltd., model: eLiPMS-3000Plus) was used with the following test parameters: 4-probe probe, electrode spacing of 2.5 mm, electrode radius of 6.5 mm, sample radius of 6.5 mm, sample mass of 2 g, and the powder resistivity was obtained by holding the pressure at 120 MPa for 3 s.
[0196] 5.Dv50 particle size test
[0197] Use Malvern 3000 laser particle size analyzer for testing. Select lithium cobalt oxide as the standard substance and water as the dispersant, and set the following instrument test parameters: test time 10s, test number 3, shading 6-15%, stirring speed 2800r / min, ultrasonic mode on, power 50%. Click the laser particle size analyzer (Malvern 3000 laser particle size analyzer) to start the test, and then add the primary sintering product or positive electrode material to the sample pool, control the amount added to adjust the shading of the sample pool to 6-15%. The instrument automatically repeats the test 3 times, and the average value of the 3 tests is taken as the mean of the test results.
[0198] 6. Electrochemical performance test
[0199] The positive electrode material to be tested: SP (Swiss Super P high conductive carbon black): polyvinylidene fluoride (PVDF) (PVDF5130 purchased from SOLVAY)) glue (mass fraction 10%, solvent N-methylpyrrolidone (NMP)) was mixed in a mass ratio of 90:5:5 on a dry weight basis, and NMP was added to make a viscous glue. The glue was coated on an aluminum foil (thickness 16 μm), and then baked in a vacuum drying oven at 120°C for 12 hours to obtain a positive electrode sheet (active material surface density 5 mg / cm 2 ). A metal sodium sheet (Aladdin) was used as the counter electrode (thickness 300±50μm). A glass fiber (Waterman) was used as the separator (thickness 675μm), and a NaPF6 solution (solvent is a mixture of EC and DMC, volume ratio EC / DMC=1:1) (Alfa) with a sodium ion concentration of 1 mol / L was used as the electrolyte. A 2032 button cell was assembled in an Ar atmosphere protection glove box.
[0200] For the prepared button battery, at room temperature of 25°C, the battery was charged at a rate of 0.1C and discharged at a rate of 0.1C in the voltage range of 2.0-4.3V to obtain the first discharge capacity of 0.1C (unit: mAh / g) by testing; then, a 45°C constant temperature button battery test cabinet was used to charge and discharge the battery at a current of 1C in the voltage range of 2.0-4.3V, and each discharge was left for 2 minutes. The charging and discharging process was repeated for 100 times, and the ratio of the 100th discharge capacity at a rate of 1C to the first discharge capacity at a rate of 1C was calculated as the capacity retention rate after 100 cycles at 1C under high temperature conditions of 45°C.
[0201] 2. Example: Preparation of positive electrode materials
[0202] Example 1
[0203] Core substrate preparation step (1): sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide are weighed according to the molar ratio of Na, Ni, Mn, and Cu being 1.04:0.42:0.51:0.09, i.e., Na and Ni are in molar excess of 0.04 and 0.02, respectively, relative to Na (x=0.02 and y=0), all raw materials are fully mixed, calcined at 950°C under 0.5MPa compressed air for 15h, and the core substrate is prepared by crushing and screening.
[0204] Coating preparation step (2): Cobalt hydroxide as a coating agent and the core substrate prepared in step (1) were weighed in a molar ratio of 1:1 between Co and the excess Ni in step (1), and the mixture was fully mixed. The mixture was calcined at 900°C under 0.5 MPa compressed air for 15 h, and the positive electrode material was obtained by crushing and screening. The particle size of the positive electrode material was 8.5 μm, and the overall composition was Na 1.04 Ni 0.42 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.51 Cu 0.09 O2.
[0205] Example 2
[0206] Core substrate preparation step (1): sodium carbonate, nickel manganese hydroxide, Ni hydroxide, and Ti are weighed in a molar ratio of Na, Ni, Mn, Cu, and Ti of 1.06:0.48:0.45:0.05:0.05, i.e., Na and Ni are in molar excess of 0.06 and 0.03 (x=0.03 and y=0) relative to Na. 0.5 Mn 0.5 (OH)2, nickel hydroxide, copper hydroxide, and titanium dioxide, all raw materials are fully mixed, calcined at 1000°C under 0.5MPa compressed air for 10 hours, and the core substrate is prepared by crushing and screening.
[0207] Coating preparation step (2): Cobalt hydroxide as a coating agent and the core substrate prepared in step (1) are weighed in a molar ratio of 1:1 between Co and the excess Ni in step (1), and are fully mixed. The mixture is calcined at 980°C under 0.5 MPa compressed air for 10 h, and the positive electrode material is obtained by crushing and screening. The particle size of the positive electrode material is 10.6 μm, and the overall composition is Na 1.06 Ni 0.48 Mn0.45 Cu 0.05 Ti 0.05 Co 0.03 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.03, and the core composition can be approximately expressed as NaNi 0.45 Mn 0.45 Cu 0.05 Ti 0.05 O2.
[0208] Example 3
[0209] Core substrate preparation step (1): Sodium carbonate, copper carbonate, nickel carbonate, manganese carbonate, titanium carbonate, and nickel carbonate are weighed in a molar ratio of Na, Ni, Mn, Ti, and Cu of 1.04:0.51:0.40:0.10:0.01, i.e., Na and Ni are in molar excess of 0.04 and 0.02 (x=0.02 and y=0) relative to Na. 0.01 Ni 0.49 Mn 0.40 Ti 0.10 CO3, and nickel hydroxide, all raw materials are fully mixed, calcined at 900°C under 0.5MPa compressed air for 20h, and the core substrate is prepared by crushing and screening.
[0210] Coating preparation step (2): Cobalt hydroxide as a coating agent and the core substrate prepared in step (1) are weighed in a molar ratio of 1:1 between Co and the excess Ni in step (1), and are fully mixed. The mixture is calcined at 850°C under 0.5 MPa compressed air for 20 h, and the positive electrode material is obtained by crushing and screening. The particle size of the positive electrode material is 9.3 μm, and the overall composition is Na 1.04 Ni 0.51 Mn 0.40 Ti 0.10 Cu 0.01 Co 0.02 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.49 Mn 0.40 Ti 0.10 Cu 0.01 O2.
[0211] Example 4
[0212] Core substrate preparation step (1): sodium carbonate, nickel manganese hydroxide, Ni hydroxide, and Ti are weighed according to a molar ratio of Na, Ni, Mn, Cu, and Ti of 1.02:0.41:0.40:0.10:0.10, i.e., Na and Ni are in excess of 0.02 and 0.01, respectively, relative to Na (x=0.01 and y=0). 0.50 Mn 0.5 (OH)2, nickel hydroxide, copper oxide, and titanium dioxide, all raw materials are fully mixed, calcined at 850°C under 0.5MPa compressed air for 28h, and the core substrate is prepared by crushing and screening.
[0213] Coating preparation step (2): Cobalt hydroxide as a coating agent and the core substrate prepared in step (1) were weighed in a molar ratio of 1:1 between Co and the excess Ni in step (1), and fully mixed. The mixture was calcined at 800°C under 0.5 MPa compressed air for 28 h, and the positive electrode material was obtained by crushing and screening. The particle size of the positive electrode material was 6.4 μm at Dv50, and the overall composition was Na 1.02 Ni 0.41 Mn 0.4 0Cu 0.10 Ti 0.10 Co 0.01 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.01, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.40 Cu 0.10 Ti 0.10 O2.
[0214] Example 5
[0215] Core substrate preparation step (1): sodium carbonate, nickel manganese hydroxide, and nickel hydroxide are weighed according to the molar ratio of Na, Ni, Mn, Cu, Ti, Fe, Al, Y, Mg, Zn, Zr, and Sn being 1.02:0.41:0.40:0.05:0.05:0.04:0.01:0.01:0.01:0.01:0.01:0.01, i.e., Na and Ni are in excess of 0.02 and 0.01, respectively, relative to Na (x=0.01 and y=0). 0.50 Mn 0.5 (OH)2, nickel hydroxide, copper oxide, titanium dioxide, ferric oxide, aluminum hydroxide, yttrium oxide, magnesium carbonate, zinc oxide, zirconium dioxide, and tin dioxide, all raw materials are fully mixed, calcined at 900°C under 0.5MPa compressed air for 15h, and the core substrate is prepared by crushing and screening.
[0216] Coating preparation step (2): Cobalt hydroxide as a coating agent and the core substrate prepared in step (1) were weighed in a molar ratio of 1:1 between Co and the excess Ni in step (1), and were fully mixed. The mixture was calcined at 800°C under 0.5 MPa compressed air for 15 h, and the positive electrode material was obtained by crushing and screening. The particle size of the positive electrode material was 8.8 μm and the overall composition was Na 1.02 Ni 0.41 Mn 0.4 0Cu 0.05 Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 Co 0.01 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.40 Cu 0.05 Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 O2.
[0217] Example 6
[0218] A positive electrode material was prepared in a manner similar to Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to a molar ratio of Na, Ni, Mn, and Cu of 1.04:0.422:0.51:0.09, that is, Na and Ni were respectively in molar excess of 0.04 and 0.022 relative to Na (x=0.02 and y=0.1); and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to a molar ratio of Co to the excess Ni in step (1) of 1.1:0.9.
[0219] The overall composition of the prepared positive electrode material is Na 1.04 Ni 0.422 Mn 0.51 Cu 0.09 Co 0.018 O 2+δ , the coating composition is Na2Ni1.1 Co 0.9 N α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.51 Cu 0.09 O2.
[0220] Example 7
[0221] The positive electrode material was prepared in a manner similar to Example 1, except as follows: in the core substrate preparation step (1): sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to a molar ratio of Na, Ni, Mn, and Cu of 1.04:0.418:0.51:0.09, that is, Na and Ni were respectively in molar excess of 0.04 and 0.018 relative to Na (x=0.02 and y=-0.1); and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to a molar ratio of Co to the excess Ni in step (1) of 0.9:1.1.
[0222] The overall composition of the prepared positive electrode material is Na 1.04 Ni 0.418 Mn 0.51 Cu 0.09 Co 0.022 O 2+δ , the coating composition is Na2Ni 0.9 Co 1.1 N α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.51 Cu 0.09 O2.
[0223] Comparative Example 1
[0224] The positive electrode material was prepared in a manner similar to Example 1, except as follows: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to a molar ratio of Na, Ni, Mn, and Cu of 1.04:0.41:0.51:0.10, that is, Na and Ni were in molar excess of 0.04 and 0.02, respectively, relative to Na (x=0.02 and y=0).
[0225] The overall composition of the prepared positive electrode material is Na 1.04 Ni 0.42 Mn 0.51 Cu0.10 Co 0.02 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.39 Mn 0.51 Cu 0.10 O2.
[0226] Comparative Example 2
[0227] The positive electrode material was prepared in the same manner as in Example 2, except that in the core substrate preparation step (1), sodium carbonate, nickel manganese hydroxide, and Ni hydroxide were weighed according to the molar ratio of Na, Ni, Mn, Cu, and Ti being 1.08:0.49:0.45:0.05:0.05, that is, Na and Ni were in molar excess of 0.08 and 0.04, respectively, relative to Na (x=0.04 and y=0). 0.5 Mn 0.5 (OH)2, nickel hydroxide, copper hydroxide, and titanium dioxide.
[0228] The Dv50 particle size of the prepared positive electrode material is 10.7 μm, and its overall composition is Na 1.08 Ni 0.49 Mn 0.45 Cu 0.05 Ti 0.05 Co 0.04 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.04, and the core composition can be approximately expressed as NaNi 0.45 Mn 0.45 Cu 0.05 Ti 0.05 O2.
[0229] Comparative Example 3
[0230] The positive electrode material was prepared in the same manner as in Example 3, except that in the core substrate preparation step (1), no Cu source was added, and sodium carbonate, nickel hydroxide, manganese dioxide, and titanium dioxide were weighed according to a molar ratio of Na, Ni, Mn, and Ti of 1.04:0.52:0.40:0.10, i.e., Na and Ni were in molar excess of 0.04 and 0.02, respectively, relative to Na (x=0.02 and y=0).
[0231] The Dv50 particle size of the prepared positive electrode material is 9.2 μm, and its overall composition is Na1.04 Ni 0.52 Mn 0.40 Ti 0.1 0Co 0.02 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.50 Mn 0.40 Ti 0.10 O2.
[0232] Comparative Example 4
[0233] The positive electrode material was prepared in the same manner as in Example 4, except that in the core substrate preparation step (1), sodium carbonate, nickel manganese hydroxide, and Ni hydroxide were weighed according to the molar ratio of Na, Ni, Mn, Cu, and Ti being 1.01:0.405:0.40:0.10:0.10, that is, Na and Ni were in molar excess of 0.01 and 0.005, respectively, relative to Na (x=0.005 and y=0). 0.50 Mn 0.5 (OH)2, nickel hydroxide, copper oxide, and titanium dioxide.
[0234] The Dv50 particle size of the prepared positive electrode material is 6.4 μm, and its overall composition is Na 1.01 Ni 0.405 Mn 0.40 Cu 0.10 Ti 0.10 Co 0.005 O 2+δ , the coating layer composition is Na2NiCoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.005, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.40 Cu 0.10 Ti 0.10 O2.
[0235] Comparative Example 5
[0236] The positive electrode material was prepared in the same manner as in Example 5, except that in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed in a molar ratio of Co to the excess Ni in step (1) of 0.8:1.
[0237] The Dv50 particle size of the prepared positive electrode material is 8.9 μm, and its overall composition is Na 1.02 Ni0.41 Mn 0.40 Cu 0.0 5Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 Co 0.008 O 2+δ , the coating composition is Na2NiCo 0.8 N α O 4+β , where 0<α<1, 0<β<2, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.40 Cu 0.05 Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 O2.
[0238] Comparative Example 6
[0239] The positive electrode material was prepared in the same manner as in Example 5, except that in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed in a molar ratio of Co to the excess Ni in step (1) of 1.2:1.
[0240] The Dv50 particle size of the prepared positive electrode material is 8.5 μm, and its overall composition is Na 1.02 Ni 0.41 Mn 0.40 Cu 0.0 5Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 Co 0.012 O 2+δ , the coating composition is Na2NiCo 1.2 N α O 4+β , where 0<α<1, 0<β<2, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.40 Cu 0.05 Ti 0.05 Fe0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 O2.
[0241] Comparative Example 7
[0242] The positive electrode material was prepared in the same manner as in Example 1, except that in the substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed in a molar ratio of Na, Ni, Mn, and Cu of 1:0.40:0.51:0.09, i.e., in a ratio (x=0) such that neither Na nor Ni was excessive relative to Na; and in the coating layer preparation step (2), no cobalt source was added (i.e., no coating was performed) and only sintering was performed.
[0243] The Dv50 particle size of the prepared positive electrode material is 10.5 μm, and its composition is NaNi 0.40 Mn 0.51 Cu 0.09 O2.
[0244] Comparative Example 8
[0245] The positive electrode material was prepared in the same manner as in Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed in a molar ratio of Na, Ni, Mn, and Cu of 1:0.40:0.51:0.09, i.e., in a ratio (x=0) in which neither Na nor Ni was excessive relative to Na; and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed in a molar ratio of Co to the core substrate prepared in step (1) (i.e., the amount of Na element used in step (1)) of 0.02.
[0246] The Dv50 particle size of the prepared positive electrode material is 10.3 μm, and its overall composition is NaNi 0.40 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ , the coating layer is composed of CoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.51 Cu 0.09 O2.
[0247] Comparative Example 9
[0248] The positive electrode material was prepared in the same manner as in Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed in a molar ratio of Na, Ni, Mn, and Cu of 1:0.42:0.51:0.09, i.e., Na was not excessive and Ni was in molar excess of 0.02 relative to Na; and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed in a molar ratio of Co to the core substrate prepared in step (1) (i.e., the amount of Na element used in step (1)) of 0.02.
[0249] The Dv50 particle size of the prepared positive electrode material is 10.6 μm, and its overall composition is NaNi 0.42 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ , the coating layer is composed of CoNiN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.40 Mn 0.51 Cu 0.09 O2.
[0250] Comparative Example 10
[0251] The positive electrode material was prepared in the same manner as in Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed in a molar ratio of Na, Ni, Mn, and Cu of 1.04:0.40:0.51:0.09, i.e., a molar excess of Na of 0.04 and no excess of Ni relative to Na; and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed in a molar ratio of Co to the core substrate prepared in step (1) (i.e., the amount of Na element used in step (1)) of 0.02.
[0252] The Dv50 particle size of the prepared positive electrode material is 10.6 μm, and its overall composition is Na 1.04 Ni 0.40 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ , the coating layer is composed of Na2CoN α O 4+β , where 0<α<1, 0<β<2, the molar ratio of coating layer to core is 0.02, and the core composition can be approximately expressed as NaNi 0.40 Mn0.51 Cu 0.09 O2.
[0253] Figure 1-3 Scanning electron microscope (SEM) images of the cathode materials prepared in Examples 1-3 at a magnification of 10,000 times are shown respectively, which clearly show that coating occurs in the obtained cathode materials.
[0254] Figure 4 The XRD spectra of the core substrate and the final positive electrode material prepared in Example 4 are shown. According to the XRD standard card: PDF#54-0887 (O3 phase), Figure 4 It can be seen that the main body of the material is O3 phase (that is, the core and the coating layer are both O3 phase structures). The difference between the two is that the core substrate shows NiO impurity peaks before coating, while there are no NiO impurity peaks after coating.
[0255] Figure 5 The first charge and discharge curve of the positive electrode material prepared in Example 5 at room temperature at a rate of 0.1C is shown, which shows a relatively gentle charge and discharge platform behavior.
[0256] The properties of the positive electrode materials prepared in Examples 1-7 and Comparative Examples 1-10 are shown in Table 1 below.
[0257] As can be seen from Table 1, in Examples 1-7, excess nickel source and excess sodium source were used in the preparation of the inner core substrate by one calcination. As a result, the inner core substrates obtained had obvious nickel oxide impurity peaks and had high residual alkali contents (all greater than 0.5%), indicating that the excess nickel and sodium existed on the surface of the material in the form of impurities at this time; after adding the cobalt source for two calcinations for coating, the NiO impurity peak disappeared in the obtained positive electrode material, and the residual alkali contents were significantly reduced (all less than 0.31%), indicating that Co consumed NiO and the residual alkali Na at the same time. In contrast, in Comparative Example 7, both sodium and nickel were not excessive during the first calcination, and as a result, although a relatively low residual alkali content (0.376%) was shown after the first calcination, the Ni impurity phase was still shown; after the second calcination, the NiO impurity peak disappeared, but the residual alkali content slightly increased to 0.395%; in Comparative Example 10, nickel was not excessive and sodium was excessive during the first calcination to prepare the inner core substrate, and as a result, the obtained inner core substrate had no nickel oxide impurity phase, but a high residual alkali content. After adding a cobalt source and coating it with the second calcination, the nickel oxide impurity phase disappeared, and the residual alkali content was slightly reduced but still high.
[0258] Comparative Examples 2, 3, and 9 still have obvious nickel oxide impurities after two sintering coating, which respectively indicates that when the coating amount is too high to x=0.04 (Comparative Example 2), due to the large amount of nickel oxide impurities in the core substrate, even two sintering coating cannot eliminate the nickel oxide impurities; when the positive electrode material does not contain Cu and the composition does not meet the requirements (Comparative Example 3), the impurities cannot be effectively eliminated; when there is not too much sodium in the core substrate (Comparative Example 9), even if a cobalt source is added for two sintering coating, the nickel impurities cannot be eliminated.
[0259] In addition, the comparison between Example 1 and Comparative Examples 1 and 7-10, the comparison between Example 2 and Comparative Example 2, the comparison between Example 3 and Comparative Example 3, the comparison between Example 4 and Comparative Example 4, and the comparison between Example 5 and Comparative Example 5 show that when the positive electrode material has a defined composition, including a defined overall composition, a coating layer composition, and a molar ratio of the coating layer to the core, the obtained positive electrode material has excellent electronic conductivity and can achieve an improved 0.1C first discharge capacity and improved 1C high temperature 45°C cycle performance.
[0260]
[0261] Table 2 shows the percentage of the main elements Ni, Co, Mn, and Cu in the surface (coating layer) of the positive electrode materials prepared in Examples 1-7 obtained by EDS analysis relative to the sum of the amounts of Ni, Co, Mn, and Cu in terms of atomic percentage. It can be seen from the results in Table 2 that the molar ratio of Ni to Co in the coating layer is approximately 1:1, and the percentage of each element basically satisfies the Na2Ni 1+y Co 1- y A α O 4+β composition.
[0262] Table 2
[0263]
[0264] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the inventive concept of the present invention, improvements can be made to the present invention, but these all belong to the protection scope of the present invention.
Claims
1. A positive electrode material for a sodium ion battery, comprising: a layered oxide core and a layered oxide coating formed on the core, The positive electrode material has the following composition as a whole: So 1+2x Ni u+x(1+y) Co x(1-y) M 1-u O 2+δ The coating layer is represented by the following formula: Na2Ni 1+y Co 1-y A α O 4+β And the molar ratio of the coating layer to the core is x, in x=0.01-0.03, u=0.40-0.49, y = -0.10 to 0.10, M is at least two elements selected from the group consisting of metal elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, including Cu and Mn, δ = -0.40 to 0.40, A is a part or all of the elements selected from the M elements, 0<α<1, 0<β<2。 2 . The cathode material according to claim 1 , wherein y=−0.05 to 0.05, such as y=−0.02 to 0.02, such as 0.
3. The positive electrode material according to any one of claims 1 to 2, wherein M is at least two elements selected from the group consisting of metal elements Cu, Fe, Mn, Ti, Mg, Zn, Al, Zr, Sn, and Y. 4 . The cathode material according to claim 1 , wherein M comprises Cu, Mn and Ti.
5. The positive electrode material according to any one of claims 1 to 4, wherein the A element is the same as the M element.
6. The positive electrode material according to any one of claims 1 to 5, wherein in the overall composition formula of the positive electrode material, the subscript of the Mn element is 0.30-0.59, such as 0.40-0.51, the subscript of the Cu element is 0.01-0.20, such as 0.01-0.10, and the subscript of the Ti element is 0-0.20, such as 0.01-0.
10. 7 . The cathode material according to claim 1 , wherein no NiO peak is present in the X-ray diffraction spectrum of the cathode material.
8. The cathode material according to any one of claims 1 to 7, wherein the core has the following composition: Pretty u M 1-u-αx O 2+γ in: u, α and x are as defined in claim 1; and γ = -0.40 to 0.
40.
9. The cathode material according to any one of claims 1 to 8, wherein the residual alkali content of the cathode material is less than 0.5%, such as 0.1-0.5%, such as 0.1-0.4%. 10 . The cathode material according to claim 1 , wherein the core is an O3 phase structure, and the coating layer is an O3 phase structure.
11. The cathode material according to any one of claims 1 to 10, wherein the cathode material has a Dv50 particle size of 1 to 100 μm, for example 5 to 20 μm.
12. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 11, comprising the following steps: Preparation of the inner core: Na source, Ni source and M source are uniformly mixed according to the molar ratio of Na, Ni and M elements of (1+2x):(u+x(1+y)):(1-u), and first sintered at a first temperature of 850-1000° C. in an oxygen-containing atmosphere, followed by cooling, and optionally crushing and screening to obtain an inner core substrate, wherein the Na source and the Ni source are molar excesses of 2x and x(1+y) respectively relative to the composition stoichiometry of the inner core; and Preparation of the coating layer: The prepared core substrate and the Co source are uniformly mixed according to the molar ratio of the excess Ni element amount and the Co element amount in the preparation of the core (1+y) / (1-y), and then sintered in an oxygen-containing atmosphere at a second temperature of 800-980°C lower than the first temperature, followed by cooling and optionally crushing and screening to obtain the positive electrode material.
13. The method according to claim 12, wherein The Na source is one or more selected from the following compounds: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, sodium chloride, sodium sulfate and sodium oxide; The Ni source is one or more selected from the following compounds: nickel carbonate, nickel nitrate, nickel acetate, nickel oxalate, nickel hydroxide, nickel sulfate, nickel chloride, nickel oxide, manganese nickel hydroxide, copper nickel manganese titanium carbonate; The M source is provided in the form of a carbonate, nitrate, sulfate, oxalate, acetate, chloride, hydroxide, oxide, or a combination thereof of the M element; and The cobalt source is one or more selected from the group consisting of cobalt carbonate, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt hydroxide, cobalt sulfate, cobalt chloride, and cobalt oxide.
14. The method according to any one of claims 12 to 13, wherein the first sintering is performed for 10 to 48 hours, such as 10 to 30 hours, and the second sintering is performed for 10 to 48 hours, such as 10 to 30 hours.
15. The method according to any one of claims 12 to 14, wherein the second temperature is 10-150°C, such as 20-100°C, lower than the first temperature.
16. A positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the positive electrode material for a sodium ion battery according to any one of claims 1 to 11. 17 . A sodium ion secondary battery comprising the positive electrode composition according to claim 16 .
18. Use of the sodium ion secondary battery according to claim 17 in energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
Citation Information
Patent Citations
Core-shell structure gradient nickel-cobalt-manganese ternary positive electrode material precursor and preparation method thereof
CN108793268A
Layered high-nickel positive electrode material with core-shell structure and preparation method of layered high-nickel positive electrode material
CN114792794A
Coated layered oxide sodium ion battery positive electrode material with excellent cycle stability
CN116247194A
Coated modified sodium ion layered positive electrode material and preparation method thereof
CN116314704A
Ternary positive electrode material of lithium ion battery and preparation method of ternary positive electrode material
CN117334852A
Cited By
Positive electrode material for sodium-ion battery, preparation method therefor, positive electrode composition, sodium-ion secondary battery, and use thereof
WO2026119244A1